Lymph Node Count After Preoperative Radiotherapy Is an Independently Prognostic Factor For Pathologically Lymph Node-Negative Patients With Rectal Cancer - Li, Qingguo (Medicine (Baltimore), 2015)
Recent studies indicated that preoperative radiotherapy significantly reduces the lymph nodes (LNs) harvest from patients with rectal cancer. This may weaken the prognostic value of current standard of LNs retrieval (≥12 LNs). This study investigates the prognostic impact of the LN counts on pathologically LN-negative (ypN0) after preoperative radiotherapy for patients with rectal cancer. Surveillance, Epidemiology and End Results (SEER) registered nonmetastatic rectal cancer patients diagnosed between 1998 and 2005 were included in this study. Optimal cutoff value for number of LNs retrieved was determined by X-tile program. Log-rank tests were adopted to compare the rectal cause specific survival (RCSS) for ypN0 patients using separated cutoff value of LN counting from 2 to 20. Correlation between LN count and tumor regression was investigated in an additional 221 patients from Fudan University Shanghai Cancer Center (FUSCC). The results showed that there were fewer number of LNs examined in patients with preoperative radiotherapy than those without (8.9 vs 10.9, P < 0.001). X-tile program identified the difference in survival was most significant (maximum of χ(2) log-rank values) for the number 4. And 5-year RCSS increased accordingly with the cutoff values ranging from 4 to 15, which were confirmed as optimal cutoff and validated as independent prognostic factors in multivariate regression analysis (χ(2) = 50.65, P < 0.001). Patients in FUSCC set were found to have fewer LNs retrieval in group of good tumor regression than in that of poor one (P = 0.01). These results confirmed the reduced number of LN retrieval in patients with rectal cancer treated with preop-RT. LN count is still an independently prognostic factor for ypN0 rectal cancer.